The Social Mobility and “Hidalguía” of the Villafañe y Guzmán Family Reflect the Intricacies of Social and Colonial Dynamics over Five Centuries - Jorge Hugo Villafañe (Histories, 2024)
This study examines the relationship between social mobility and hidalguía (noble status) in Castile and America over five centuries, focusing on a specific family of peninsular hidalgo individuals, the Villafañe y Guzmán family, who exerted significant influence in the provinces of La Rioja and Córdoba (Argentina) through their kinship ties. The distribution of resources, power, and opportunities has been instrumental in determining the social status and opportunities available to individuals and groups. The study confirms that the limited social mobility in colonial society and the advantages of accessing certain activities may explain the enduring nature of socioeconomic inequality in Latin America.